Historic leaves. - Somerville Historical Society (Somerville, Mass.) (Tufts University. Tisch Library., 2015)
1 online resource (9 v.) : ill.; Vol. 3 of 8.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.